Shared power and fairness in trust-based supply chain relationships in an urban local food system. Issue 3 (28th January 2020) - Nakandala, Dilupa; Smith, Meg; Lau, Henry
Abstract : Purpose: The purpose of this paper is to investigate supply chain relationships in an urban local fresh food system from a retailer perspective to examine the types of relationships and the factors underpinning the development of such relationships. Design/methodology/approach: Using the multiple case study method, interview data from twelve urban local fresh food retailers in Sydney were analysed using the thematic analysis. Findings: This study finds that balanced power relationships in the supply chain allow reasonable power to sit with growers in product price determination irrespective of the dependency of small-scale growers on relatively large local retailers. Trust-based relationships are developed over multiple transactions, where shared values across the supply chain and consistently low opportunistic behaviour in reward sharing are demonstrated to be the crucial factors underpinning close relationships. This study also found evidence of horizontal supply chain linkages among retailers in a competitive environment. Practical implications: Findings of this study have implications for policymakers in designing urban fresh food systems and for practitioners in large urban retailers including supermarkets that attempt to integrate local food into their product portfolio. Originality/value: This study extends the local food system literature dominated by rural studies to include new knowledge about the dynamics of collaborations in contemporary urban local fresh food supply chains. It provides the first empirical evidence of lateral inventory transshipment between retailers in a competitive environment confirming previous simulation studies.